The path of political reform in light of the Arab Spring Jordan as a model - Mahmoud Tahboub, Naser (Opción, 1970)
Six years after the so-called Arab Spring and its negative repercussions on Jordan, especially on economic, reform efforts emerged that formed foundations and rules that were later built on the foundations of political reform, namely parliamentary elections and party and party life. Election laws and the parties that organize them, and these foundations are represented in the legal and legislative environment that took place during the years of the Arab Spring to work to make them more harmonious through the implementation of constitutional amendments and the establishment of an independent commission. All these foundations led to a review of previous electoral and party experiences, as well as the laws governing party life and electoral processes, to benefit from them, leading to the 2016 elections, which were the culmination of political reform efforts over the past six years.